Comparative analysis of medications for local treatment of burns on national and foreign markets - В. V. Vons; M. B. Chubka; T. A. Groshovyi; I. P. Stechyshyn (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Burn wound treatment issues remain relevant in modern medicine, since burns are among the most common types of injuries and rank third among all types of injury in peacetime. The problem of treatment of burn injuries are determined by the high frequency of their occurrence, the complexity and duration of treatment of such patients, with serious consequences. To date, in the world there are a large number of drugs for local treatment of burns in various forms (ointments, gels, creams, aerosols, solutions for external use, patches) and biological drugs are also used. The aim of the work was to conduct a comparative analysis of the range of registered medicinal products for local treatment of burns on the national market, with preparations of this segment of the market, registered in Georgia and France. Georgia is a country, which is not a member of the European Union, and France is one of the five countries leading exporters of medicines and is a member of the European Union, in order to determine the relevance and feasibility of developing new drugs. In the analysis of drugs registered in the pharmaceutical markets of France and Georgia, those drugs that have no analogues in Ukraine, for the most part are patches (patches), considering in more detail. The study of the nomenclature assortment of drugs carrying out in accordance with the State Register of drugs and the Anatomical-Therapeutic-Chemical Classification, as an information source was used Compendium, online-directories and online-pharmacу. According to the results of the research conducted on the end of 2018, in Ukraine there are about 105 drugs, production in various forms that is directly used for local treatment of burns. In the pharmaceutical markets of Georgia and France, this amount of drugs is respectively 101 and 64 drugs. In all three countries, most medications for local treatment of burns presented in soft drugs, in particular, in Ukraine 67.58%, in Georgia 84.16% and in France 39.06%, respectively. In Ukraine, 58.33% of all drugs for local treatment of burns domestically produced, but in Georgia and France, the proportion of such drugs is significantly lower, namely 11.88% and 32.81% respectively. The comparative analysis conducted by us proved that in the pharmaceutical markets of France and Georgia there were registered drugs in the form of patches that are widely used in the treatment of burn injuries, the analogues of which are absent in Ukraine. These studies prove the prospect of expanding the range of existing ursus forms and creating a new group of original drugs that would stimulate regenerative skin processes and improve wound healing.